Comprehensive Transcriptome and Metabolic Profiling of Petal Color Development in Lycoris sprengeri - Yang, Feng; Li, Chao-han; Das, Debatosh; Zheng, Yu-hong; Song, Tao; Wang, Lan-xiang; Chen, Mo-Xian; Li, Qing-zhu; Zhang, Jianhua (Frontiers in Plant Science, 2021)
Lycoris sprengeri (L. sprengeri) is an important ornamental bulbous plant, and its numerous varieties in different color forms are widely planted. Multiple color types of petals in L. sprengeri provide us with possibilities to delineate the complicated metabolic networks underlying the biochemical traits behind color formation in this plant species, especially petal color. In this study, we sequenced and annotated a reference transcriptome of pink and white petals of L. sprengeri and analyzed the metabolic role of anthocyanin biosynthesis in regulating color pigment metabolism. Briefly, white and pink petal samples were sequenced with an Illumina platform, to obtain the reads that could be assembled into 100,778 unique sequences. Sequences expressed differentially between white vs. pink petals were further annotated with the terms of Gene Ontology (GO), Clusters of Orthologous Groups (COG), Kyoto Encyclopedia of Genes and Genomes (KEGG), and eggNOG. Gene expression analyses revealed the repression of anthocyanin and steroid biosynthesis enzymes and R2R3 MYB transcription factor (TF) genes in white petals compared to pink petals. Furthermore, the targeted metabolic profiling of anthocyanins revealed that color-related delphinidin (Del) and cyanidin (Cy) pigments are lower in white petals, which correlate well with the reduced gene expression levels of anthocyanin biosynthesis genes. Taken together, it is hypothesized that anthocyanin biosynthesis, steroid biosynthesis, and R2R3 MYB TFs may play vital regulatory roles in petal color development in L. sprengeri. This work provides a valuable genomic resource for flower breeding and metabolic engineering in horticulture and markers for studying the flower trait evolution of L. sprengeri.